The relationship between the severity of dental caries and the nutritional status of children - Murphy, Cillian (Trigin Institute, 2022)
Nutritional status is a factor that can determine the quality of human resources. Factors associated with nutritional status include health status and level of consumption of nutrients. Dental caries is a disease that can affect the nutritional condition of the child so that it can cause nutritional problems. Consumption levels of nutrients such as carbohydrates, proteins and fats are not only related to nutritional status but may also be associated with the severity of dental caries. The sample used in this study amounted up to 50 people. Based on the multivariate test results obtained that the level of carbohydrate consumption is a factor confounding the relationship between the severity of dental caries and the nutritional status of students in grade two. The school is expected to increase participation in the school canteen in the provision of nutritious foods and to increase the involvement of teachers in providing information about the behavior of clean and healthy. For further research it is expected to examine the variables that were not examined in this study. The school is expected to increase participation in the school canteen in the provision of nutritious foods and to increase the involvement of teachers in providing information about the behavior of clean and healthy. For further research it is expected to examine the variables that were not examined in this study. The school is expected to increase participation in the school canteen in the provision of nutritious foods and to increase the involvement of teachers in providing information about the behavior of clean and healthy. For further research it is expected to examine the variables that were not examined in this study.